The Phonetics of Mandarin Tones in Conversation - Brenner, Daniel Scott (The University of Arizona., 2015)
Mandarin tone categories are universally thought to center on pitch information, but previous work (Berry, 2009; Brenner, 2013) has shown that pitch cues reduce in the conversational context, as do the other concurrent cues such as duration or intensity that secondarily signal tone categories. This dissertation presents two experiments (an isolated word perception experiment, and a dictation experiment) aimed at discovering how Mandarin listeners deal with these reduced cues under everyday conversational conditions. It is found that detailed spectral information is far more useful in the perception of Mandarin tones—both in isolated words and in the perception of full conversational utterances—than pitch contours, and that the removal of pitch from the recordings does not greatly influence perception of the tone categories.